The Corinthian correspondence: redaction, rhetoric, and history - Hughes, Frank Witt (Lexington Books/Fortress Academic, 2021)
The partition and redaction of 2 Corinthians -- The need to partition 1 Corinthians -- The redaction of 1 Corinthians -- Letter A : troubles in worship (1 Corinthians 11:2-34a + 16:1-4 + 11:34b) -- Letter B : the body matters (2 Cor 6:14-7:1 + 1 Cor 6:12-20 + 1 Cor 9:24-10:22 + 1 Cor 15:1-58 + 1 Cor 16:13-24) -- Letter C : arguing for unity (1 Cor 1:1-6:11 + 7:1-8:13 + 9:19-23 + 10:23-11:1 + 12:1-31a + 14:1c-33a + 12:31b-13:13 + 16:5-12) -- Letter D : reorganizing the offering (2 Cor. 8:1-24) -- Letter E : apology for Paul's apostleship (2 Cor 2:14-6:13 + 2 Cor 7:2-4) -- Letter F : anguish of heart and many tears (2 Cor 10:1-12:13 + 1 Cor 9:1-18 + 2 Cor 12:14-13:13) -- Letter G : consolation for the afflicted (2 Cor 1:1-2:13 + 2 Cor 7:5-16 + 2 Cor 13:11-13) -- Letter H : an appeal to the Achaians (2 Corinthians 9:1-15) -- Redirecting Paul's ministry -- The publication of 1 and 2 Corinthians : from scroll to codex.